Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn417
|View full text |Cite
|
Sign up to set email alerts
|

Motivation

Abstract: Motivation underlies much perception, cognition, and behavior. As such, it is studied from many levels of analysis within psychology and neuroscience. In this chapter, we review research and theory on the psychology of motivation from the perspective of social emotive neuroscience, which is an integrative approach involving social/personality psychology, psychophysiology, affective neuroscience, and the study of emotions and motivation within humans. More specifically, this chapter reviews theory and research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…The important implication is that the body, and how the body was used in previous interactions, plays a crucial role for the instigation of approach/avoidance tendencies. Although others before us have highlighted the embodiment of approach/avoidance states (e.g., Harmon-Jones, Price, & Harmon-Jones, 2014), conclusive evidence for a grounding in whole-body movement was missing, due to the fact that locomotive behavior is typically confounded with particular visual changes. In fact, Rougier and colleagues (2018) showed that visual cues of whole-body locomotion can trigger approach-avoidance tendencies even if the participant was stationary.…”
Section: Discussionmentioning
confidence: 94%
“…The important implication is that the body, and how the body was used in previous interactions, plays a crucial role for the instigation of approach/avoidance tendencies. Although others before us have highlighted the embodiment of approach/avoidance states (e.g., Harmon-Jones, Price, & Harmon-Jones, 2014), conclusive evidence for a grounding in whole-body movement was missing, due to the fact that locomotive behavior is typically confounded with particular visual changes. In fact, Rougier and colleagues (2018) showed that visual cues of whole-body locomotion can trigger approach-avoidance tendencies even if the participant was stationary.…”
Section: Discussionmentioning
confidence: 94%